Implementasi Pendidikan Karakter Islam di Sekolah Dasar Islam Terpadu Ikhtiar Makassar - PALILI, SAMPARA (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2018)
This article explores the Implementation of Islamic Character Education in Millenial Era in Integrated Islamic Elementary School Ikhtiar Makassar; the approach used is qualitative descriptive and collecting data through: 1) Observation, 2) Interviews and 3) documentation directly at the Locus of Research. The results of the research carried out illustrated that the SDIT efforts in shaping the character of its students in accordance with the character of Islam and the goal of national education in millenial era carries out various efforts in daily routines in schools, those were: 1) through fostering faith and piety to Allah, 2) through learning process, 3) through the implementation of flag ceremonies and 4) through the enforcement of school rules, attitudes and culture. The values ​​of Islamic characters that are created in these 4 activities include: 1) Love, Obedience, and obeying the commands of Allah and His Messenger, 2) love of science, respect for teachers, cooperation, diligence, confidence, discipline, obedience to regulations agreed, 3) homeland love, nationalism, patriotism and idealism and 4) siddiq character, fathanah, trust, tabligh and just and humble